THE PROCESSES OF PREHNITIZATION IN BASITES OF KOROSTEN PLUTON - ZINCHENKO, O.; MYTROKHYN, O.; SAVENOK, S.; PICHUHIN, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2005)
The mineral composition of plagioclase alteration products in Korosten Pluton basic rocks have been characterized on the base of X-ray diffraction and X-ray fluorescence analuses.